The Analysis of Social Action in Assassin’s Creed: Renaissance's Main Character - Almahdi, Muhammad Zaidan (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This research explores the various forms of social action exhibited by the protagonist, Ezio Auditore, in Oliver Bowden's novel Assassin's Creed: Renaissance. Drawing from Max Weber's theory of social action, the research categorizes these actions into four types: instrumental rationality action, value-oriented action, affective action, and traditional action. The data for the study consists of sentences, paragraphs, and dialogues describing Ezio Auditore's social actions in the novel, analyzed using a descriptive method with a sociology of literature approach. The data analysis reveals the frequency of each action type, with affective action being the most prevalent by ten data, followed by value rational action with eight data, rational instrumental action with five data, and traditional action with two data. Additionally, the study identifies four main goals pursued by the character: seeking revenge, uncovering conspiracies, eradicating the Templar order, and protecting Florence. The predominant use of rational instrumental action and the lower occurrence of value rational action in pursuing these goals are highlighted. These findings offer insights into Ezio Auditore's motivations and behaviors, shedding light on the social dynamics depicted in the novel.